2021
DOI: 10.5603/fm.a2020.0041
|View full text |Cite
|
Sign up to set email alerts
|

The terminal branch of the posterior interosseous nerve: an anatomic and histologic study

Abstract: Background: The aim of this study was to evaluate the terminal branch of the posterior interosseous nerve (PIN) by anatomically and histologically assessing the number, dimension, and area of its individual fascicles, by determining the dimension and area of the whole nerve itself, and by calculating the nerve density ratio (ratio of the sum of the areas of individual fascicles to the area of the whole nerve) of the terminal branch of the PIN. Methods: Twenty-eight terminal branches of the PIN nerve samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Ten (35.7%) nerves contained a single bundle of nerve fibers, while 18 (64.3%) had at least two bundles of nerve fibers (from two to nine). However, the study found no statistically significant relationship between gender and the size of the nerves and the number of bundles they contained [38].…”
Section: Missankov Et Al Examining Fifty-eight Upper Limbsmentioning
confidence: 59%
“…Ten (35.7%) nerves contained a single bundle of nerve fibers, while 18 (64.3%) had at least two bundles of nerve fibers (from two to nine). However, the study found no statistically significant relationship between gender and the size of the nerves and the number of bundles they contained [38].…”
Section: Missankov Et Al Examining Fifty-eight Upper Limbsmentioning
confidence: 59%
“…Anatomic studies on the association between PIN and the supinator muscle exist [4][5][6][7][8][9][10][11][12][13][14]. However, detailed information on the precise point of branching out of the radial nerve to innervate each posterior compartment muscle in the forearm with the superficial branch is needed.…”
Section: Introductionmentioning
confidence: 99%